Consumer Protection of Unauthorized Cosmetic Distribution in Indonesia's E-Commerce - Muthia Sakti; Dinda Dinanti (Universitas Ahmad Dahlan, 2020)
Introduction to the Problem: Technological advances in the field of pharmacy or medicine, especially in the field of cosmetics today, have provided many alternatives for consumers, especially women, to meet their needs. The presence of various cosmetic products does provide hope for women to look more beautiful and attractive. But often, many cosmetics products have no active ingredients mentioned. Motivated by big profits, the manufacturers do not register their products for further assessment. When it comes to the market, the products are actually without standard authorization, or in the other cases using false or fictitious marketing authorization numbers. One form of protection to the consumer is the certainty of information contained in cosmetic packaging itself. The distribution of cosmetics without marketing authorization is also commonly found in applications or online stores. Still, on the one hand, it makes it easier for the public to conduct business transactions. However, compared with the easiness the online stores offered, when the products are still unauthorized, it will harm its users.Purpose/Objective Study: This research discusses consumer protection for the circulation of cosmetics without marketing authorization in Indonesia through e-commerce.Findings:This research shows that the Indonesian government protects consumers against the circulation of cosmetics without marketing authorization through the rules and laws. However, on the other aspect, those rules or regulations have no practical impact on society in this digital era. So, Indonesia should concern more to online activity where unauthorized marketing products are being marketed.